MEKANISME PENETAPAN MASYARAKAT PENERIMA BANTUAN PANGAN NON TUNAI (BPNT) DI KELURAHAN SICINCIN KECAMATAN PAYAKUMBUH TIMUR KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Sembi Novela; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The determination of BPNT recipient communities is carried out by the Ministry of Social Affairs of the Republic of Indonesia. The determination is in accordance with the results of data collection carried out in the field. The purpose of this study was to determine and explain the mechanism for determining the recipients of the Non-Cash Food Assistance Program (BPNT) in Sicincin Village, Payakumbuh Timur District and to determine the inhibiting factors and supporting/supporting factors in determining the recipients of the Non-Cash Food Assistance (BPNT) in Sicincin Village, Sub-District. East Payakumbuh. The theory used in this study is the theory of structural functionalism proposed by Robert King Merton, which is about the real (manifest) and hidden (latent) functions. This type of research uses descriptive qualitative research methods. The subjects of this study amounted to 4 people consisting of the Head of the Village, Head of Kesos and Ekbang, Head of RT 002, and Chair of PSM as well as the Verval Team. Sources of data used are primary data sources and secondary data. Data collected by data collection techniques in the form of observation, interviews, and documentation. Analysis of the data used in this study in the form of data reduction, data presentation and conclusion. The results of this study are the mechanism for determining BPNT recipients starting with data collection for poor families (KK), then surveying the priorities of the Head of Family (KK) recipients of BPNT and then determining BPNT recipients carried out by the Ministry of Social Affairs. Keywords: Aid, Poor, BPNT Recipient